Implementation of a mixed model of in-person and virtual prenatal care during the COVID-19 pandemic at the National Maternal Perinatal Institute in Lima-Peru - Meza-Santibañez, Luis (2021)
The coronavirus 19 (COVID-19) pandemic and the measures implemented for its control meant the interruption of prenatal care, with potential risk to maternal and fetal health. However, conventional in-person prenatal would imply exposure and risk of infection in patients and health care providers. The Instituto Nacional Materno Perinatal (INMP) has incorporated teleconsultation as part of a new model of mixed prenatal care, which aims to reduce in-person appointments and, therefore, the contact and risk of viral transmission. The prenatal care package performs essential activities to care for pregnant women of specific gestational ages with a greater impact on perinatal and maternal outcomes. This new model could be generalized nationally and be part of the solution to the disparities of healthcare in Peru, through policies for the use of telemedicine in prenatal care that facilitate its implementation, as well as its sustainability after the COVID-19 pandemic.